CO-OPTIMIZED SOLAR–WIND–STORAGE DISPATCH STRATEGIES FOR GRID STABILITY AND COST MINIMIZATION - Pathak, Hiren Chandrakant (International Journal of Engineering Technologies and Management Research, 2024)
The increased energy consumption in the renewable energy has contributed to the modern-day power systems to be dependent more on the fluctuating sources of power such as the solar energy and wind energy. These sources are clean and sustainable; however, their intermittence creates certain issues to offer grid stability and economic functionality. The following paper outlines a co-optimistic dispatch model, that transforms solar power, wind power, and battery energy storage system (BESS) to make such grid reliable and therefore, cost-effective of operation overall. The multi-objective framework is planned to take into consideration the use of energy supply, uncertainty prediction, scheduling storage, and peak load in order to handle the load energy. The proposed plan implies that the synchronous dispatch may be employed to efficiently reduce the curtailment, control frequency and voltage state, and need to utilize the expensive divulged fossil generators as little as possible. The findings placed emphasis on intelligent scheduling, foresight forecasting, and energy storage as an aspect of having an effective, cheap renewable power system in place.